Evaluation of SQ 34,514: pharmacokinetics and efficacy in experimental herpesvirus infections in mice. - Braitman, A (1991)
The new antiviral nucleoside SQ 34,514 [(1R-1 alpha, 2 beta, 3 alpha)-2-amino-9- [2,3-bis(hydroxymethyl)cyclobutyl]-6H-purin-6-one], the active R isomer of racemic SQ 33,054 (cyclobut-G), was evaluated for efficacy in the treatment of herpesvirus infections in mice. SQ 34,514 was orally efficacious in a herpes simplex virus type 1 (HSV-1) systemic infection, an intracerebral HSV-2 infection, a vaginally induced HSV-2 infection in ovariectomized mice, and in a systemic murine cytomegalovirus infection. SQ 34,514 compared favorably with acyclovir and ganciclovir in the treatment of these experimental infections. In mice, SQ 34,514 had an oral bioavailability of 80% based on urinary excretion. SQ 34,514 may have potential value in the therapy of HSV and cytomegalovirus infections in humans.